Analysing Energy Systems Integration: A Socio-Technical Approach and a System Architecture Methodology (2022)
ABSTRACT: Chapter 7 posits the integration of energy systems by considering the coupling of natural gas and heating. This chapter presents energy system integration as a methodological approach to understanding the architecture of this sort of systems.